2020
DOI: 10.1108/ijwbr-07-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on firm adaptation: the case of the wine industry

Abstract: Purpose The purpose of this study was to test the effects of climate change, as manifested in both temperature and rainfall changes, on adaptive practices in a sample of wine firms operating in South Australia. Given that firms’ adaptation to the external environment can be advanced through effective internal learning systems, a further purpose was to explore the moderating effect of absorptive capacity. Design/methodology/approach The authors used a survey as well as secondary sources to collect data. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In recent years, the wine industry has undergone notable changes, shifting from traditional methods to adopting more eco-friendly and sustainable practices. This trend is driven by environmental challenges such as changing weather patterns and alterations in grape maturation processes, which highlight the need for sustainable approaches (Galbreath et al. , 2020; Jobin Poirier et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the wine industry has undergone notable changes, shifting from traditional methods to adopting more eco-friendly and sustainable practices. This trend is driven by environmental challenges such as changing weather patterns and alterations in grape maturation processes, which highlight the need for sustainable approaches (Galbreath et al. , 2020; Jobin Poirier et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the wine industry has undergone notable changes, shifting from traditional methods to adopting more eco-friendly and sustainable practices. This trend is driven by environmental challenges such as changing weather patterns and alterations in grape maturation processes, which highlight the need for sustainable approaches (Galbreath et al, 2020;Jobin Poirier et al, 2021;Naulleau et al, 2021). Moreover, recent studies indicate that the European viticulture sector is increasingly focusing on sustainability as a central business strategy, pointing to a deliberate effort to improve environmental practices (Ouvrard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is wine important from economic and cultural standpoints, but the industry is also facing profound changes and complex challenges. Recent studies have shown that the wine industry faces challenges such as climate change (Galbreath et al , 2020), global competition (Anderson and Wittwer, 2013; Balogh and Jámbor, 2017; Rainer et al , 2023), economic fluctuations (Ben Ameur et al , 2022; Jiao, 2017), changing consumer preferences, sustainability and environmental concerns (Moscovici et al , 2022), trade barriers (Mariani and Pomarici, 2019), supply chain issues and increasing costs (Mariani et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These products, characterized by layers of volatile odors, flavors, and oral-somatosensory sensations on a multisensory level, could hold critical importance for achieving consumer approval ( Wang and Spence, 2018a , b ). If effectively harnessed to cater to specific target audiences, crossmodal communication might thus not only help to bolster marketing strategies and consumer contentment but also serve as a tool for optimizing the use of resources within complex food products, potentially contributing to the broader goal of reducing food waste ( Galbreath et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%